CUSTOMARY LAW TOWARD MATAMUSAN DETERMINATION TO CUSTOM SOCIETY AT WEWIKU WEHALI, BELU, NTT - Bria, Roswita Nelviana (Jurnal Ilmiah Bahasa dan Sastra, 2014)
Abstract Customary law is the law or unwritten rule that grow and thrive in a society that is only obeyed bycostom society in Belu. One of the most important customary law in Belu is the marriage law. Matrilineality system in south Belunese descent is traced through the mother and maternal ancestors.However, in this matrilineal system, there is still a customary law that maintains the fatherâs lineage based on customary law by adopting which called matamusanwhich is really inerestingÂ because it is dfferent with matrilineal system in Minangkabau as the most popular matrilineal society. The research design of this thesis is descriptive qualitative research. It is intended to describe about matamusan as customary adoption system, chronological step of matamusan determination, the development of matamusan implementation, factors influencing the development of matamusan determination, and the effectiveness of customarylaw toward matamusandetermination.From the result of this study, it was clear that customary law is still effective in handle the violation of matamusan determination.Â Key words :Â Customary Law, Custom Society, Matamusan Determiantion and WewikuÂ Â Wehali